Untangling the Hymenaea stigonocarpa complex (Fabaceae) using population genetics and morphology - Pinto, Rafael Barbosa; Ferreira, Ramilla Dos Santos Braga; Goncalves, Ariany Rosa; Telles, Mariana Pires De Campos; Chaves, Lazaro Jose; Rezende, Andreia Alves [UNESP]; Diniz-Filho, Jose Alexandre Felizola; Mansano, Vidal De Freitas (Oxford Univ Press, 2023)
Hymenaea is a genus of Fabaceae easily recognized by vegetative characteristics. However, the circumscription of some species has been historically challenging. The tangled circumscription of H. stigonocarpa has been addressed in several molecular and morphological studies, but some of the morphological confusion has yet to be resolved. Thus, in this study we used population genetics coupled with detailed morphological analyses to improve taxonomic definition in this complex, currently comprising two varieties (H. stigonocarpa vars. stigonocarpa and brevipetiolata). Bayesian and population genetic structure analyses were conducted using nine nuclear microsatellite loci for 1034 individuals from 35 populations. The morphometric analyses were performed using leaflet characters. Our results support the existence of five genetically structured clusters, and morphometric analyses support the recognition of two clusters, emphasizing H. stigonocarpa var. brevipetiolata as an exclusive genetic and morphological group, encouraging us to make changes in its taxonomic ranking. Thus, we propose the adoption of specific status for H. stigonocarpa var. brevipetiolata on the basis of its population genetics and morphology. In addition to the population genetics data and morphological analyses, a taxonomic treatment with illustrations is provided.
Keywords: Cerrado; Jatoba; morphology; population genetics; species delimitation; taxonomy